1999
DOI: 10.1063/1.123146
|View full text |Cite
|
Sign up to set email alerts
|

Controlled tuning of the radiative lifetime in InAs self-assembled quantum dots through vertical ordering

Abstract: Multilayer structures of InAs quantum dots have been studied by means of photoluminescence techniques. A strong increase of the radiative lifetime with increasing number of stacked dot layers has been observed at low temperatures. Moreover, a strong temperature dependence of the radiative lifetime, which is not present in the single layer samples, has been found in the multistacked structures. The observed effects are nicely explained as a consequence of the electronic coupling between electrons and holes indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
25
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 76 publications
(32 citation statements)
references
References 12 publications
7
25
0
Order By: Relevance
“…A large red-shift has been observed [21] in QD structures where the QDs vertically interact more strongly than in the present case, due to the smaller spacer thickness (6.2 nm instead of 10 nm). Recently, it has been shown [22,23] that Coulomb interaction between carriers inside the dot can explain this behavior: in particular, detailed calculations of electron and hole confining energies (performed on stacked arrays similar to our structures) versus the number of stacked QD layers indicate that the competing effects of Coulomb interaction and vertical coupling account for the observed drastic blue-shift when spacers 10 nm thick are used. Indeed, when a second layer is added, with 10 nm thick spacers, carrier wavefunction delocalization [23] produces a drastic decrease in the Coulomb interaction energy (blue-shift); successive layers favour the formation of minibands which, in turn, reduce (red-shift) the ground state transition energy (the QD "gap").…”
Section: Resultsmentioning
confidence: 99%
“…A large red-shift has been observed [21] in QD structures where the QDs vertically interact more strongly than in the present case, due to the smaller spacer thickness (6.2 nm instead of 10 nm). Recently, it has been shown [22,23] that Coulomb interaction between carriers inside the dot can explain this behavior: in particular, detailed calculations of electron and hole confining energies (performed on stacked arrays similar to our structures) versus the number of stacked QD layers indicate that the competing effects of Coulomb interaction and vertical coupling account for the observed drastic blue-shift when spacers 10 nm thick are used. Indeed, when a second layer is added, with 10 nm thick spacers, carrier wavefunction delocalization [23] produces a drastic decrease in the Coulomb interaction energy (blue-shift); successive layers favour the formation of minibands which, in turn, reduce (red-shift) the ground state transition energy (the QD "gap").…”
Section: Resultsmentioning
confidence: 99%
“…Such an alignment has been widely reported for stacked layers of SK self-assembled InAs/GaAs QDs [9,10], and has also been exploited in the fabrication of columnar dots [11] and quantum posts [12]. Electronic coupling in columnar dots, quantum posts, and in stacked layers of QDs [13,14] allows the fabrication of dots with height/base-length aspect ratios of ∼1, or even >>1 (quantum wires), with consequent control over the confinement and polarization properties.…”
Section: Introductionmentioning
confidence: 99%
“…This latter phenomena is responsible for the decrease of the PL decay time when increasing the spacer layer thickness. Numerous studies done by colocci et al [7], on vertically coupled InAs/GaAs QDs have shown a complete delocalisation of the hole wave function over the coupled dot column with layer separation varied between 10 and 15 nm, and they have shown, in the same conditions, a substantial localisation of the electron wave function within each dot. .…”
Section: Fwhm (Mev)mentioning
confidence: 96%
“…The gradual localisation of the carriers may be responsible for the decrease of the PL decay time with increasing the inter-layer separation distance. Indeed, since the radiative lifetime is inversely proportional to the squared electron and hole wave func- tion overlap [7,8 ], the delocalisation of the hole wave function over the hole dot column induces a decrease of the electron and wave function overlap. This latter phenomena is responsible for the decrease of the PL decay time when increasing the spacer layer thickness.…”
Section: Fwhm (Mev)mentioning
confidence: 99%